PEMBERDAYAAN KELOMPOK TANI PADI DI DESA IKHWAN KECAMATAN DUMOGA BARAT KABUPATEN BOLAANG MONGONDOW - NURHAMIDIN, ANISA NURHANIFAH; TULUSAN, FEMMY; RURU, JOORIE (JURNAL ADMINISTRASI PUBLIK, 2020)
Farmer empowerment is all efforts to improve the ability of farmers to carry out better farming through education and training, counseling and assistance, development of systems and means of marketing agricultural products, consolidation and guarantee of agricultural land area, easy access to knowledge, technology and information, and strengthening farmer institutions. Farmer group is a social unit consisting of two or more people who carry out intensive and regular interactions, so that between them there is a division of tasks, structures, and certain norms that are specific to that unity. In this study using a type of qualitative research in which this research is descriptive in nature that is conducting indepth interviews collecting primary data and collecting secondary data, which then results of primary and secondary data are processed and data will be obtained. The results showed that the problem that hampered the empowerment of rice farmers in the Ikhwan Village was the assistance program provided by the government such as rice seedlings that were not well suited to the soil structure in the Ikhwan Village and with the inappropriate assistance had an impact on the quality of crops that were not good for farmers rice in the Ikhwan Village. The government had already provided training on good farming practices and pest management, but that had taken place 4 years ago. The problem hampering the empowerment of farmer groups in the Ikhwan village is also about the scarce fertilizer and the price that is difficult for farmers to reach because of the scarcity of fertilizer. The government has also sought a way out so that the rice farmers' group in the Ikhwan village does not have a dispute because of the impact of the government assistance program. Finally, due to the lack of training provided by the government, only farmer group meetings were held to discuss the problems faced by rice farmers in the Ikhwan village. Keywords: Empowerment, Farmer Group, Program.